ANALISIS KEBUTUHAN KOLEKSI PEMUSTAKA DI PERPUSTAKAAN UNIVERSITAS ATMA JAYA YOGYAKARTA - C. Esmi Triningsih; A. Prastowo Harsa Pamardi (Program Studi Perpustakaan dan Ilmu Informasi, Fakultas Bahasa dan Seni, Universitas Negeri Padang, 2023)
The collection needs survey is aimed at finding out what collections users need. It is hoped that the survey results can help the collection development department in procuring library materials so that the collections provided are in accordance with needs. Data collection was carried out by distributing questionnaires to respondents using Google Form so that it was time efficient and data recapping was automatic. Respondents consisted of a total of 612 UAJY lecturers and students, all processed using SPSS 20. Quantitative descriptive data analysis and the results obtained showed that the majority of respondents visited the library once a week. This is not impossible because in the current digital era, information can be accessed easily via the internet network anytime and anywhere. The majority of users' needs for visiting the library are to do their final assignments, followed by looking for references and coursework. The types of collections that are much sought after are theses/final assignments, then e-journals, journals and e-books. Subjects that are of great interest are economics, social, political, cultural, technical, language and fiction. In terms of the recency, suitability and availability of the collection, the UAJY Library has been able to meet the expectations of users as shown by the large percentage, the recency of the collection is 82.4%, the suitability of the collection is 80.2% and the availability of the collection is 76.1%. There are suggestions for several collection subjects that need to be added and books with certain authors. Apart from that, the UAJY library needs to increase access to international journals and journal collections with subjects that suit the needs of study programs.